ANALISIS PENGARUH PUNGUTAN LIAR TERHADAP PENETAPAN HARGA PASAR KAYU OLAHAN DI KABUPATEN MIMIKA - Purwaningsih .; Joko Suparyono (JURNAL KRITIS (Kebijakan, Riset, dan Inovasi), 2017)
The aim of this research is to understand the effects of extortion towards processed wood’s market prices in Mimika Regency. This research applied the calculation formula of cost-based pricing, which is the mark-up pricing and the cost-plus pricing. Firstly, the author counted all the cost components of processed wood and used the formulas to decide the price of processed wood. Then the result of it, used to compare the profit margins obtained by processed wood entrepreneurs in Mimika Regency. Overall, the result of the study shows; first, the mark-up pricing gives effect towards processed wood’s market prices in Mimika Regency; Second, the extortion towards the entrepreneurs does not increase the processed wood’s market prices but instead reduce the profit margins of entrepreneurs.